Evaluation of use of hyperbaric oxygen in suppression of hyper-proliferation in hypoxic NSCLC cells: Suppression of hyper-proliferation in hypoxic NSCLC cells - Chen, Jiun-Rung; Khan, Haseeb; Umarzai, Yigiter; Rajput, Abbaas; Mamund, Tokalp (Cellular and Molecular Biology, 2023)
Hyperbaric oxygen therapy (HBO) is being researched as a potential adjuvant treatment for solid malignancies, such as NSCLC. It can reduce tumour hypoxia and has been found to slow tumour growth, stop dedifferentiation, and reduce apoptosis resistance in hypoxic NSCLC cells. Though HBO has shown promise in treating various cancers, more study is required to determine its precise mechanism of action in NSCLC. Analyze the effect of hyperbaric oxygen on the growth of hypoxic non-small cell lung cancer cells. We used the NSCLC cell lines A549 and H1299 to analyze aerobic glycolysis in vitro. Warburg effect testing included glucose absorption, lactate, adenosine triphosphate (ATP), and pyruvate measurements. Using a quantitative glycolytic flow model, we also analyzed the effect of HIF-1-induced genes on the flux of glucose metabolism. Lewis lung carcinoma (LLC) animal models in C57BL/6J mice were used to examine the development of lung tumours. The effects of pcDNA and HIF1A on glucose uptake, lactate production, pyruvate, and ATP levels were studied in A549 and H1299 NSCLC cells. While A549's glucose absorption increased over time, H1299's was dramatically decreased by HBO treatment. The pyruvate levels were more significant in H1299, particularly in hypoxia, and were lowered by HBO. In A549, the lactate content was more effective. After HBO treatment, glucose absorption was reduced while intracellular ATP levels were maintained. Overexpression of HIF-1a was able to counteract the effect of HBO on glycolytic gene expression. PFKP is a possible therapeutic target because HBO reduces the Warburg effect in NSCLC cells by downregulating HIF-1.